Hydrolysis rates of biodegradable plastics by the gastric fluid and enzymatic activities of the gastric fluid of the edible crab Cancer pagurus - Lukas Miksch; Lars Gutow; Reinhard Saborowski (PANGAEA, 2023)
The hydrolytic degradation of biodegradable and conventional plastics by the gastric fluid of the edible crab Cancer pagurus were assayed in-vitro with pH Stat titration. Suspensions of different microplastics were incubated with gastric fluid at 15 °C in artificial seawater. Rates of hydrolysis, as determined by counter-titration with a diluted base (NaOH), was recorded for two hours. The gastric fluid was separated by anion exchange chromatography into 65 fractions. Again, three pools of fractions were tested for their hydrolytic potential with a plastic based on polylactic acid at 30°C. Enzyme assays with fluorogenic substrates were performed with each of the 65 fractions of the gastric fluid. Methylumbelliferone derivatives of fatty acid esters (MUF-butyrate, MUF-heptanoate and MUF-oleate) were used as substrates in buffer at different pH ranging from 5 to 9 and at a temperature of 25°C. The increase in fluorescence was measured with a microplate reader. Analogously, the effect of a detergent (sodium dodecyl sulfate) on the enzymatic activity was measured. All measurements were conducted under controlled laboratory conditions.